Pengaruh Komunikasi Electronic Word of Mouth terhadap Brand Awareness Warung Kopi Pagi-Sore (WKPS) Berau - Rangga Yl. Setiawan; Rina Juwita; Kezia Arum Sary; Ziya Ibrizah (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study examines the effect of Electronic Word of Mouth (e-WOM) communication on the brand awareness of Warung Kopi Pagi Sore (WKPS), a local coffee-shop micro, small, and medium enterprise (MSME) in Berau Regency, East Kalimantan. The rapid growth of digital platforms such as Instagram, Google Maps, and WhatsApp has positioned consumers not only as message receivers but also as communicators who share reviews, experiences, and recommendations. This research used a quantitative approach with a survey method. Data were collected from 100 respondents selected through non-probability purposive sampling, based on the criterion of being at least 17 years old and familiar with WKPS through digital media. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4. The measurement model showed that all indicators were valid (outer loading > 0.70; AVE > 0.50) and reliable (Cronbach’s Alpha and Composite Reliability > 0.70). The structural model produced a path coefficient of 0.878, a T-statistic of 27.562 (> 1.96), and a P-value of 0.001 (< 0.05), indicating that e-WOM has a positive and significant effect on brand awareness, with an R-Square of 0.770. These findings confirm that consumer-generated digital communication functions as a horizontal, credible communication channel that strengthens brand recognition, recall, and consideration. The study contributes theoretically to Brand Equity theory and practically offers guidance for local coffee-shop MSMEs in optimizing digital word-of-mouth strategies to build brand awareness at low cost.